Avaliação clínica , laboratorial e hemogasométrica de cadelas e neonatos em parto distócico e cesariana eletiva. - Leonardo Dias Mam?o (2018)
During the neonatal period, the mortality rate in small animals is high, which may reach 30%, and this percentage is due to the inability to carry out the correct clinical evaluation and also the lack of technical knowledge about neonatology. Veterinary follow-up in the peri-natal period may increase neonatal survival by controlling or eliminating factors that may contribute to increased morbidity and mortality. The aim of this study was to evaluate pregnant bitches at the moment of dystocic and elective cesarean section birth through clinical, laboratory and hemogasometric parameters and evaluate and compare the neonates born by dystocia and elective cesarean delivery using hemogasometry, serum lactate, Apgar scores and clinical evaluations. Also, evaluate the interference of the birth order of neonates and evaluate if the anesthetic protocol used in this study was safe for bitches and neonates. Thirteen pregnants bitches in labor (6 elective caesarean and 7 dystocia) were used, of races, weights and varied ages, and 30 canine newborn (18 elective caesarean and 12 dystocia) were divided into two distinct groups of bitches and neonates: elective caesarean section (GCE) and dystocia (GD). The bitches were evaluated through clinical, laboratorial and hemogasometric parameters before surgery, and neonates, evaluated through clinical evaluations, Apgar score, serum lactate and hemogasometry over the five pre-established periods: T0- moment of birth, T1- three hours after, T2- six hours after, T3- 12 hours after and T4- 24 hours after. In the evaluation of bitches, there was difference between the groups only in potassium, in which the CGE presented higher values in relation to the GD. It was also observed that the GCE bitches presented several acid-base disorders, but in GD, metabolic acidosis predominated. In relation to the neonates, bradycardia, tachypnea and hypothermia in both groups were evidenced at birth. In the Apgar score at birth, there were predominant neonates without distress (55.6%) and some with moderate distress (38.8%) in the CGE, while in the GD, the majority presented severe distress (83.3%). However, three hours later, almost 100% of neonates in both groups were no longer in distress. Hyperlactatemia and hyperglycemia were also evidenced in neonates of GD. Mixed acidosis (metabolic and respiratory) was evidenced at birth in most neonates in both groups. There was no difference in the order of birth of neonates in any of the groups evaluated. There was a strong correlation between blood urea nitrogen (Bun) and bicarbonate between bitches and neonates of the elective caesarean group. In the dystocia group, there was a strong correlation in Bun, sodium, chlorine and glucose between bitches and neonates. It can be concluded that the dystocia bitches present lower potassium values in relation to the elective cesarean section. It was also concluded that elective caesarean bitches may present with various acid-base disorders (respiratory alkalosis, respiratory acidosis, mixed disorders and metabolic acidosis), however, bitches in dystocia have a predominance of metabolic acidosis. In relation to the neonates, it was concluded that the main acid-base disorder observed at birth was mixed acidosis (metabolic and respiratory) in both groups. In addition, acid-base disorders in neonates in dystocia are more severe and recovery is slower than neonates born by elective caesarean section. It is also possible to conclude that at birth neonates in dystocia present higher hyperlactatemia and lower Apgar score (greater distress) in relation to those born in elective cesarean section. However, three hours later, there are no differences in these variables between groups. There was no difference in the birth order of neonates in any of the groups evaluated (elective caesarean section and dystocia). Serum progesterone dosage has been shown to be an effective method for establishing the correct timing of submitting female dogs to elective caesarean. Finally, it is concluded that the anesthetic protocol used in this study was safe for both bitches and neonates